Determining the acoustic field distribution of ultrasonic multi-element probes - Krzysztof Opieliński; Tadeusz Gudra (Archives of Acoustics, 2014)
The paper presents a universal method of determining the distribution of acoustic field of multi-element probes designed for applications in ultrasound transmission tomography (UTT). This method allows us to calculate the acoustic field for different sectors of the probe with assigned geometry of elementary transducers’ location. The idea is to sum acoustic fields generated by all elementary transducers with the use of geometrical transformations of coordinates of location of the discussed points of the acoustic field against each of the transducers. In order to verify the calculation results measurements of acoustic field distribution were also carried out for selected sectors of these probes. On the basis of an analysis of calculation results the size of electronically switched transmitting sector was optimized (in the sense of the number of concurrently radiating elementary transducers) for a linear and a ring ultrasonic multi-element probes from the point of view of their use for visualizing the inside of a biological structure by means of UTT.